EKSISTENSI TEKNOLOGI PENDIDIKAN DALAM INOVASI PEMBELAJARAN - Suhirman Suhirman (Universitas Islam Negeri Fatmawati Sukarno, 2016)
Technology education is a complex and integrated process that includes: human, environmental, systems, tools, ideas, procedures and organization. Technology education in the journey, is a solution and anticipatory, by providing solutions to overcome the problem of learning and prepare students for a better life in the future, because life in the days to come, full of competition and challenges, necessitating their learning innovations, Therefore, the existence of educational technology has a strategic role in preparing learners who have a competitive edge in competition, both from within and from abroad